Simulasi Penjadwalan Proyek Pembangunan Jembatan Gantung dengan Metode Monte Carlo - Santony, Julius (Jurnal Informasi dan Teknologi, 2020)
The scheduling of a suspension bridge construction project is very influential in determining the success of construction which has risks and uncertainties in the construction of a suspension bridge. So we need a suspension bridge project scheduling to predict the work schedule for each suspension bridge construction activity. To overcome all the risks and uncertainties in the construction of a suspension bridge, a Monte Carlo method simulation is needed to process 10 activities in a suspension bridge construction project. The accuracy rate using Monte Carlo simulation is 93.99% for predictions for 2017, 2018 for 98.77% and 86.75% for 2019. So this Monte Carlo simulation can be used in predicting the scheduling of a suspension bridge construction project.